Spontaneous Splenic Rupture and Rituximab-Induced Acute Thrombocytopenia in a Patient with High-Risk Mantle Cell Lymphoma - Jared Williams; Shingi Chiruka (Case Reports in Hematology)
Mantle cell lymphoma is a relatively rare type of mature B-cell non-Hodgkin’s lymphoma with an incidence of approximately 8 cases per million persons per year. In patients with mantle cell lymphoma, there are rare case reports of the potentially life-threatening consequences of splenic rupture and rituximab-induced acute thrombocytopenia (RIAT) occurring separately, but there are no reports of these occurring in the same patient. Whilst rare, they are important to be aware of as early detection may prevent fatal outcomes.